Rethinking Complicity in the Surveillance of Sex Workers: Policing and Prostitution in America's Model City - Stem, Scott W. (2020)
This Note uncovers a history that has been largely ignored, dismissed, and sometimes even intentionally obscured: the history of the policing of sex workers in the twentieth century. When most lawyers think about the surveillance of sex workers, they think of a standard cast of characters: police, prosecutors, pimps, purchasers, and procurers. But the surveillance of sex workers has always been much broader and renders a far greater number of actors complicit. This Note uncovers the significant (yet often overlooked) roles played by four groups in surveilling sex workers: (1) the federal government, (2) elite women, (3) public health authorities, and (4) major universities. As a case study, the Note focuses on the city of New Haven, Connecticut, during the twentieth century